Pengaruh Implementasi Kebijakan, Kepemimpinan, dan Kompetensi terhadap Penerimaan Pajak Bumi dan Bangunan pada UPT Pajak Daerah Kelas A Citeureup Kabupaten Bogor - Mochamad Dika Lathifuddin; A.H. Rahadian (Jurnal Pajak Vokasi (JUPASI), 2026)
The phenomenon of Land and Building Tax Revenue at the Class A Citeureup Regional Tax UPT, Bogor Regency has not been effective. The study aims to analyze and evaluate the Influence of the Policy Implementation, Leadership Policies, and Competence toward Land and Building Tax Revenue at the Class A Citeureup Regional Tax UPT, Bogor Regency partially and simultaneously. This study uses a quantitative research type with an explanatory approach. The research population of Bappenda employees of Bogor Regency to assess the implementation of the duties and functions of the Class A Citeureup Regional Tax UPT, Bogor Regency, amounted to 529, with Slovin (5% significance level) obtaining 228 samples. The data analysis technique uses multiple linear regression analysis techniques. Research results: (1) There is a positive and significant influence of partial policy implementation toward Land and Building Tax revenue at the Class A Citeureup Regional Tax UPT, Bogor Regency, with a magnitude of influence of 56,48%. (2) There is a positive and significant influence of partial leadership toward Land and Building Tax revenue at the Class A Citeureup Regional Tax UPT, Bogor Regency, with a magnitude of influence of 43.29%. (3) There is a positive and significant influence of partial competence toward Land and Building Tax revenue at the Class A Citeureup Regional Tax UPT, Bogor Regency, with a magnitude of influence of 65.29%. (4) There is a positive and significant influence of policy implementation, leadership, and competence simultaneously toward Land and Building Tax revenue at the Class A Citeureup Regional Tax UPT, Bogor Regency, with an Adjusted R Square influence of 75.8% and the remaining 24.2% influence from other factors but not researched. Keywords: Work Planning; Service Innovation; Performance Evaluation; Civil Servant Performance.